2022
DOI: 10.1111/1365-2745.13864
|View full text |Cite
|
Sign up to set email alerts
|

Plant foliar nutrient response to active layer and water table depth in warming permafrost soils

Abstract: 1. Thawing permafrost in northern latitudes has led to deepening active soil layers and fluctuating water tables. This could increase plant access to permafrostderived nitrogen (N), phosphorus (P) and other nutrients such as calcium (Ca) and magnesium (Mg), and subsequently increase plant productivity and ecosystem carbon storage and nutrient cycling. We hypothesized that deepening permafrost thaw and water table fluctuations would alter species-specific foliar N:P ratios. Since there is often more P, Ca an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…The sampling was performed between mid-August and early September 2019 (i.e., at the late-season period). For both sites, leaf samples were dried at 60 • C and ground (Jasinski et al, 2022;Natali et al, 2011;Schuur et al, 2007).…”
Section: Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling was performed between mid-August and early September 2019 (i.e., at the late-season period). For both sites, leaf samples were dried at 60 • C and ground (Jasinski et al, 2022;Natali et al, 2011;Schuur et al, 2007).…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Since the beginning of the monitoring (in 1990), the Minimal thaw area showed less ground subsidence and little-disturbed moist acidic tundra and is dominated by the sedge E. vaginatum and Sphagnum spp. mosses, coexisting with evergreen and deciduous shrubs (Jasinski et al, 2022;Schuur et al, 2007). The Moderate thaw area displays isolated areas of ground subsidence (Schuur et al, 2007) and remains dominated by the sedge E. vaginatum, with a lower moss cover than the Minimal thaw area (Jasinski et al, 2018).…”
Section: Study Sitementioning
confidence: 99%
“…Because groundwater depths can significantly influence soil nutrient concentrations in various ecosystems (Hefting et al, 2004;Miao et al, 2013;Jasinski et al, 2022;Zhang et al, 2022), we first calibrated ELM based on the groundwater table depth (WTD) simulated by ELM-170 ParFlow (Fang et al, 2022;Tran et al, 2024) in which lateral hydrological flow was simulated…”
Section: Elm Calibrationmentioning
confidence: 99%
“…Recent investigations support this, indicating that intraspecific trait variation of several tundra plant species is strongly related to microclimate, including local temperature, soil moisture content and snow conditions (Kemppinen et al., 2021; Kemppinen & Niittynen, 2022). Studies have also found that changes in local thaw depth can lead to variation in plant chemistry by altering nutrient availability and plant uptake (Blume‐Werry et al., 2019; Jasinski et al., 2022). At the same time, broad‐scale studies show consistent relationships between intraspecific trait variation and macroclimate across the tundra biome (Bjorkman et al., 2018; Kudo et al., 2001).…”
Section: Introductionmentioning
confidence: 99%